Temperature defendence of the hyperfine interaction in (NH4)2ZrF6 - Rodríguez, Agustín Mario (1983)
The thermal evolution of the hyperfine quadrupole interaction in (NH4)2ZrF6 has been investigated via TDPAC from 14 to 400 K. A phase transition is detected near 370 K. The low-temperature phase exhibits two sites equally populated for181Ta probes. The associated electric field gradients are described by both high asymmetry parameters and high interaction frequencies. On the other hand, the high-temperature phase corresponds to an unique axially symmetric and more intense electric field gradient.